VALUES ORIENTATION CHANGING IN SOCIAL BEHAVIOR OF THE ADHERENTS TAREKAT NAQSYABANDIYAH MUDZAHARIYAH - Zen Amrullah; Hoddin, Muhammad Sholeh; Belvage, Rio Heykhal (Harmoni, 2023)
Research on social change in a tarekat has been conducted by many researchers. However, the results of the research are still descriptive narrative. Therefore, this study focuses on changes in the value orientation of the behavior of Naqsyabandiyah Mudzhariyah adherents, a congregation that is widely adhered to by Madurese people, especially residents of Gersempal Omben Sampang village. As part of religious teachings, tarekat not only functions as a doctrine and dzikr ritual, but also as a social control that can shape people’s behavior. This research aims to obtain data about the Naqsyabandiyah Mudzhariyah tarekat which is influenced by the doctrine of the tarekat ‘s teachings. This research method is qualitative. Data collection techniques in this study used interviews, documentation, and observation. While for data analysis, researchers dialogued the data with the theory of Sufism and social behavior. The results of this study obtained aspects of religiosity of tarekat adherents grouped into four groups, namely the ideological dimension, the ritual dimension, the experience dimension, and the religious knowledge dimension. In addition, this study also produced findings of four social behaviors reflected in the behavior of Gersempal villagers as adherents of the Naqsyabandiyah Mudzhariyah order. 1). Ascetic orientation reflected in work ethic behavior. 2) Al-Ta’awun value orientation which is manifested in helping behavior. 3) Futuwwah value orientation, which is reflected in giving behavior, and 4). Transcendental communication which is reflected in silaturrahmi behavior. These four behaviors are the result of the accumulation of the Tarekat doctrine.